The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1590/s0034-89101994000100008
|View full text |Cite
|
Sign up to set email alerts
|

Doença de Chagas como causa básica de óbito na região sudeste do Brasil: presença de causas contributárias

Abstract: LITVOC, J. Doença de Chagas como causa básica de óbito na região sudeste do Brasil: presença de causas contributárias. Rev. Saúde Pública, 28: 69-75, 1994. Estudaram-se os atestados de pessoas falecidas no Estado de São Paulo, Brasil, em 1987, cuja causa básica foi a cardiopatia chagásica, com a finalidade de conhecer a informação adicional que está presente no atestado como "causa contributária". Foram analisadas as informações existentes em 1.308 Declarações de Óbito. As causas contributárias foram identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…We observed that the main conditions associated with death by Chagas' disease have been inserted into the group of diseases of the 15 . Consistent with the clinical descriptions and the predominance of chronic chagasic cardiopathy (CCC) as the main cause of death, cardiac complications were the main associated diseases, particularly arrhythmias/ conduction disorders, heart failure and cardiomyopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the main conditions associated with death by Chagas' disease have been inserted into the group of diseases of the 15 . Consistent with the clinical descriptions and the predominance of chronic chagasic cardiopathy (CCC) as the main cause of death, cardiac complications were the main associated diseases, particularly arrhythmias/ conduction disorders, heart failure and cardiomyopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that multiple causes and conditions often lead to death of an individual, the use of merely the underlying cause of disease is not be sufficient to describe the real epidemiological situation of a chronic condition such as Chagas' disease. In addition, the use of multiple causes of death allows identification of conditions that may be synergistic to death and opens new perspectives for the prevention and treatment of these comorbidities 2 .We observed that the main conditions associated with death by Chagas' disease have been inserted into the group of diseases of the 15 . Consistent with the clinical descriptions and the predominance of chronic chagasic cardiopathy (CCC) as the main cause of death, cardiac complications were the main associated diseases, particularly arrhythmias/ conduction disorders, heart failure and cardiomyopathies.…”
mentioning
confidence: 92%
“…Of these articles, we have classic texts by Forattini on the biology of Triatominae 63 - 68 . Studies on the burden of Chagas disease in different regions of the Country 40 , 155 , 176 , control strategies 139 - 141 , and alternative transmission types of Chagas disease 175 are also present, as well as the disease social impact and, more recently, an interesting article on the 100th anniversary of the Chagas disease description 6 .…”
Section: Introductionmentioning
confidence: 99%